The Effects of Cognitive Competence and Self Esteem Towards Students' Reading Comprehension - agustina ramadhianti (Scope : Journal of English Language Teaching, 2018)
The aim of this study is to obtain empirical data and to analyze about whether or not there are the effects of cognitive competence and self esteem towards student’s reading comprehension. The study was conducted at the State Junior High Schools in South Jakarta from November 2012 to January 2013. The research method is survey with multiple-regression analysis technique. The research findings show three points. Firstly, there is a signinificant effect of cognitive competence and self-esteem towards student’s reading comprehension with multiple coefficient correlation is 0,816. Secondly, there is a significant effect of cognitive competence towards student’s reading comprehension since tobserved is higher than ttable (4.728 > 1.669). Thirdly, there is a significant effect of self-esteem towards student’s reading comprehension since tobserved is higher than ttable (6.476 > 1.669). Based on the research findings, the student’s reading comprehension can be developed by increasing the cognitive competence and self-esteem of the students